The System of Additional Professional Education of the University as a Platform for Implementation of the Federal Project «New Opportunities for Everyone» - M. F. Galikhanov; V. V. Kondratyev; D. V. Elizarov; L. T. Miftakhutdinova (Moscow Polytechnic University, 2020)
The global task constantly represented in the documents adopted by the government is the breakthrough development of the Russian economy. The results of the "New Opportunities for Everyone" Federal project in the framework of the national "Education" project are aimed at developing human capital - a cross-cutting condition for achieving national development goals of the country (increasing life expectancy, accelerating technological development of the Russian Federation, ensuring accelerated implementation of digital technologies in the economy and social sphere, etc.). Additional professional education at Kazan National Research Technological University is considered as an integral and real part of the lifelong learning system. The University is actively involved in the implementation of the Federal project. For this purpose, about 20 additional professional development programs have been developed and implemented.